Analysis of cotton water productivity in Fergana Valley of Central Asia - Reddy, J.M.; Muhammedjanov, S.; Jumaboev, Kahramon; Eshmuratov, Davron (Scientific Research Publishing, Inc., 2012)
Cotton water productivity was studied in Fergana Valley of Central Asia during the years of 2009, 2010 and 2011. Data was collected from 18 demonstration fields (13 in Uzbekistan, 5 in Tajikistan). The demonstration field farmers implemented several improved agronomic and irrigation water management practices. The average values of crop yield, estimated crop consumptive use (ETa) and total water applied (TWA) for the demonstration sites were, respectively, 3700 kg/ha, 6360 m3/ha, and 8120 m3/ha. The range of values for TWA and ETa were, respectively, 5000 m3/ha to 12,000 m3/ha and 4500 m3/ha to 8000 m3/ha. A quadratic relationship was found between TWA and ETa. The average yield of the adjacent fields was 3300 kg/ha, whereas the average yield of cotton in Fergana Valley as a whole was 2900 kg/ha, indicating 28% and 14% increase in crop yield, respectively, from, demonstration fields and adjacent fields. There was no significant difference in crop yields between the wet years (2009 and 2010) and the dry year (2011), which is explained by the quadratic relationship between TWA and ETa. The water productivity values ranged from 0.35 kg/m3 to 0.89 kg/m3, indicating a significant potential for improving water productivity through agronomic and irrigation management interventions. The ratio of average ETa divided by average TWA gave an average application efficiency of 78% (some fields under-irrigated and some fields over-irrigated), the remaining 22% of water applied leaving the field. Since more than 60% of the water used for irrigation in Tajikistan and Uzbekistan is pumped from, even if all this 22% of water returns to the stream, substantial energy savings would accrue from improving the average application efficiency at field level. The range of values for TWA indicates the inequity in water distribution/accessibility. Addressing this inequity would also increase water productivity at field and project level.